Die enigmatiese aard van die trieksterfiguur in Ingrid Winterbach se Niggie - Marisa Botha; Helize van Vuuren (Tydskrif vir Letterkunde, 2018)
This article explores the enigmatic nature of tricksters in Ingrid Winterbach’s Niggie (Cousin, 2002), as manifested in everyday life through the supernatural and the unconscious (for instance in dreams). In this way some of the puzzling aspects of this magisterial novel are clarified. Early in Niggie the reader is confronted with a trickster figure in the form of a dream figure, the red haired woman with the little feather hat, who appears in the farmer’s epiphanic dream. After tricking him, she leaves him with an intense sense of loss. This type of trickster figure is variously embodied and manifested throughout the novel in several other mysterious characters, adding to the jouissance or playfulness and ambiguity in the novel. It would appear that Winterbach as a South African author was inspired not only by tricksters from European mythology, but also by indigenous African, Khoi and San mythology. In this regard trickster figures from the Khoi and San as well as Nguni cultures are also discussed. These figures are, amongst others, the Mantis (/Kaggen), Heitsi-Eibeb, Uthlakanyana and Tokoloshe.